Aspek Hukum dan Implikasi Pajak dalam Merger Perusahaan Gojek dan Tokopedia: Tinjauan dari Perspektif Hukum Bisnis - I Maykel Ram (Universitas Wahid Hasyim, 2025)
This study aims to analyze the legal aspects and tax implications arising from the merger process between two major technology companies in Indonesia, Gojek and Tokopedia, and to provide an overview from a business law perspective. This merger is a significant strategic move in both the Indonesian and global business world, involving various legal and fiscal considerations. Specifically, the research examines three main aspects: first, compliance with regulations governing mergers in Indonesia, such as the Limited Liability Company Law and competition laws supervised by the Business Competition Supervisory Commission (KPPU), as well as regulations concerning personal data protection; second, an analysis of the legal consequences for the companies involved, their shareholders, and other stakeholders; and third, the tax implications arising from the merging of assets and the distribution of profits, which may be influenced by changes in the company's structure. This research uses a qualitative approach with descriptive analysis based on literature studies and relevant regulations. The findings indicate that the merger between Gojek and Tokopedia requires close scrutiny regarding competition law principles to avoid violations of antitrust laws. Additionally, the tax implications of the merger include more complex tax obligations, including potential tax liabilities that had not been previously considered, which must be addressed by both companies. From a business law perspective, the merger highlights the importance of conducting thorough due diligence that encompasses legal, financial, and tax aspects to ensure long-term success. This study provides valuable insights for legal practitioners and policymakers regarding the regulation of corporate mergers in Indonesia.